Superovulation,Sychronisation of Oestrus and Embryo Transfer in CrossBred Cows - Sureshan Nair S P (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1992)
The object of the present investigation was to ascertain the influence of varying doses of FSH and PGF2₻on various parameters of superovulation and embryo collections, with the ultimate aim of fixing the optimum dose of FSH and PGF2 ₻ required for successful superovulation in crossbred cows. Detailed investigation was made in a herd of 32 crossbred cows belonging to the University Livestock Farm, attached to the College of Veterinary and Animal Sciences, Mannuthy, during the period from April 1989 to December, 1991. The animals were randomly divided into 6 groups based on 3 doses of FSH and 2 doses of PGF2 ₻ administered. It was observed that 20 mg of FSH, with 25 mg of PGF2 induced satisfactory superovulation response and 20 mg of FSH with 15 mg of PGF2 ₻ resulted in better embryo quality. Further increase in the dose did not show any improvement in the responses. Right ovary showed more response than the left. Day 11 was found to be ideal for starting superovulation treatment, and day 6 for embryo collection, though statistically no significant influence was noticed by day of collection on superovulation response. Parity and age of donors had no influence on superovulation. Rainy and summer months were found to be better seasons for superovulation treatment than winter. Shorter duration (24 hr) of oestrum was noticed in more number of animals. 20 mg of FSH and 25 mg of PGF2 ₻ (group 3) yielded better cervical dilatation and flushing efficiency. Level of progesterone increased following superovulation treatment and declined 3 days before oestrum and reached the lowest level on day of oestrum. Pregnancy rate achieved was 33.3 per cent, but calving percentage was nil.